A critical analysis of Division work conferences held in Albay from January, 1959 to December, 1961 - Ravalo, Jose R. 1922-
A critical analysis of six work conference held in the Division of Albay during a three-year period from January, 1959 to December, 1961 was presented in this study. It assessed the status of the work conference as a type of in-service education activity of the school personnel in this particular school division.